2022
DOI: 10.1177/14705958221089192
|View full text |Cite
|
Sign up to set email alerts
|

Toward a more in-depth measurement of cultural distance: A re-evaluation of the underlying assumptions

Abstract: Some 20 years ago, Shenkar (2001) criticized several of the underlying assumptions of the cultural distance (CD) construct. Despite this, researchers continue to use the same metric which fails to address many of the underlying problems. As a result, CD studies seem to generate results which are often contradictory. Rather than rejecting the distance metaphor, the main objective of this study is to provide a more in-depth measure of CD that addresses the assumptions of linearity, symmetry, equivalence, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…In their study, these authors identified similar impacts on the financial performance of different groups of foreign subsidiary firms associated with CD towards host countries with specific profiles. Correa da Cunha et al (2022) found that regardless of the different sizes of CD in each group of foreign subsidiary firms, the results revealed the same positive or negative impacts for CD towards host countries with specific cultural profiles. This evidence indicates that although cultures cannot be compared as better or worse, adjusting to certain cultural profiles in the host country might be easier for some foreign subsidiary firms than others.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In their study, these authors identified similar impacts on the financial performance of different groups of foreign subsidiary firms associated with CD towards host countries with specific profiles. Correa da Cunha et al (2022) found that regardless of the different sizes of CD in each group of foreign subsidiary firms, the results revealed the same positive or negative impacts for CD towards host countries with specific cultural profiles. This evidence indicates that although cultures cannot be compared as better or worse, adjusting to certain cultural profiles in the host country might be easier for some foreign subsidiary firms than others.…”
Section: Introductionmentioning
confidence: 90%
“…More recently, studies have shown that the effects of CD on host countries with specific profiles tend to affect the financial performance of different groups of firms in similar ways depending more on the direction than the distance size (Correa da Cunha et al, 2022). This suggests that although cultures may not be compared in terms of better or worse, the effects of certain cultural profiles in the host country might be easier for foreign subsidiary firms to adjust to, while other cultural traits can create additional challenges and conflicts, making it more difficult for foreign subsidiaries to adjust.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Correa de Cunha et al (2022) challenge not only the assumptions of symmetry but also of equivalence, finding that not all cultural dimensions have similar impacts on outcomes (Hofstede, 1989; Maseland et al , 2018; Shenkar et al , 2022), suggesting that dimensions comprising a country's cultural profile be considered as constructs in their own right. As such, we have a priori reasons to expect that the distances on the Performance Orientation (PO), Gender Egalitarianism (GE), and Assertiveness (AS) dimensions will be asymmetrically related to firm performance, as moderated by direction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Zaheer et al (2012), without considering the institutional context of the respective locations, research merely addresses how much two cultures differ but does not address how they differ. This notion was first advanced by Shenkar (2001), who called the assumption of identical distances in both directions an “illusion”, now referred to as the fallacy of symmetry assumption (Correa de Cunha et al ., 2022; Fu et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation